A novel singular-free solution based on principle of transfer theory for the hand-eye calibration problem. (April 2022) - Wang, Weidong; Liu, Yueming; Song, Huajian; Du, Zhijiang
Highlights: Singularity analysis for the solution of the hand-eye calibration. A singular-free solution of the hand-eye calibration. The solution is verified by a novel surgical robot. Abstract: For the Endoscope-assisted Surgical Robot system, the success of the surgery can be heavily determined by the accuracy of the unknown hand-eye matrix between the manipulator and the laparoscopic camera. Although many analytical solutions algorithms have been proposed, it is found that the hand-eye matrix estimated by some existing analytical solutions algorithms will deviate from its true value in some cases. Therefore, the singularity analysis for the solution of the hand-eye calibration based on orthogonal dual tensor is firstly pointed out in this paper. To avoid the above singular phenomenon, a novel singular-free solution based on Principle of Transfer theory is proposed in this paper, which can be verified by the corresponding simulation and experimental results.